DIGITAL TRANSFORMATION IN EDUCATION AND TRAINING IN VIET NAM - Linh, Duong Thanh; Tran, Le Ngoc; Phung, Nguyen Thi Khac (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
There are many different definitions of digital transformation (DT) but be understood simply as transforming human activities from the concrete world to the virtual world in the network environment. The emergence of Artificial Intelligence (AI) has had an enormous impact on life, the economy, and society, brings incredible changes in the environment, working methods, and information. As a result, people approach more information, reduce distance, narrow space, and save time. Digital transformation represents an inevitable trend, happening rapidly, and the education and training industry can not be out of that trend, despite being considered by experts to be the safest industry in the AI explosion. The article analyzes some basic contents of DT applying technology in Education and Training, the current situations, future tendencies, and proposing solutions in the new period.